1998
DOI: 10.1046/j.1365-2958.1998.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar filament elongation can be impaired by mutations in the hook protein FlgE of Salmonella typhimurium: a possible role of the hook as a passage for the anti‐sigma factor FlgM

Abstract: SummaryAmong motile revertants isolated from flagellar hookdeficient (flgE ) mutants of Salmonella typhimurium, one produced only short flagellar filaments in L broth, despite the fact that flagellin itself has the ability to polymerize into long filaments in vitro. This pseudorevertant has an intragenic suppressor, resulting in a two-amino-acid substitution (Asp-Gln→Ala-Arg) in the C-terminal region of the hook protein, FlgE. The flagellation of the pseudorevertant was greatly affected by the concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In this strain, the export of FlgM was depen- dent on the NaCl concentration. Observation of the swimming behavior of this strain at a concentration of NaCl allowing good flagellation suggested that the function of the hook had deteriorated, since the flagellar bundles were not as tight as those of the wild-type cells (25). In the case of R. sphaeroides, a strain showing a curved hook produced normal amounts of flagellin, but the swimming behavior both in swarm plates as well as in liquid medium was altered.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this strain, the export of FlgM was depen- dent on the NaCl concentration. Observation of the swimming behavior of this strain at a concentration of NaCl allowing good flagellation suggested that the function of the hook had deteriorated, since the flagellar bundles were not as tight as those of the wild-type cells (25). In the case of R. sphaeroides, a strain showing a curved hook produced normal amounts of flagellin, but the swimming behavior both in swarm plates as well as in liquid medium was altered.…”
Section: Discussionmentioning
confidence: 93%
“…The amplification product was cloned into the unique EcoRI site of pRS4303 located after amino acid 40 from the predicted FlgE sequence. The 5.5-kb PstI fragment carrying flgE::aad was subcloned into pJQ200mp18 (25). The resulting plasmid was introduced by transformation into E. coli S17-1 and subsequently transferred to R. sphaeroides by conjugation.…”
Section: Methodsmentioning
confidence: 99%
“…Following completion of the hook-basal body, secretion of the FlgM anti- 28 factor occurs by this pathway (52,108). The work presented below is a characterization of the determinants contained within FlgM that are required for it to be specifically recognized and secreted by this pathway (20).…”
Section: Flgm Secreted By a Flagellar Type III Pathwaymentioning
confidence: 99%
“…The transcriptional hierarchy of the flagellum pathway is one mechanism that leads to the efficient assembly of the flagellum following induction of the pathway. FlgM is secreted following the completion of the hook-basal body intermediate structure (52,108). This results in the full induction of class 3 promoter transcription.…”
Section: Link Between Regulation Of Expression and Efficiency Of Assementioning
confidence: 99%
“…In P. aeruginosa , the flagellar hook is formed by polymerization of approximately 120 single molecules named flagellar hook protein E (FlgE) (NP_249771), encoded by the flagellar hook protein gene, flgE (GeneID: 878285). In addition to providing flexibility and power conversion between the basal body and the filament, FlgE is also involved in the elongation or assembly of the filament, and flgE mutations often result in structural abnormality or deficiency in multiple bacterial species 1013 . However, additional roles that this protein may play, as either an isolated monomer or a polymer in the hook, remain unclear except for a few reports on the antigenicity of FlgE in bacterial infections 14–16 .…”
Section: Introductionmentioning
confidence: 99%